2019
DOI: 10.1093/rheumatology/kez087
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of infection risk with small molecule JAK inhibitors in rheumatoid arthritis

Abstract: Objectives To evaluate the risk of serious infection (SI) and herpes zoster (HZ) in rheumatoid arthritis patients receiving JAK inhibitors. Methods We conducted a systematic literature review and meta-analysis of phase II and III randomized controlled trials of tofacitinib (5 mg bid), baricitinib (4 mg od) and upadacitinib (15 mg od). Patient-exposure years were calculated. A per-protocol analysis was applied, incorporating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
1
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(174 citation statements)
references
References 44 publications
12
138
1
13
Order By: Relevance
“…Baricitinib, at therapeutic dosing (either as 2 mg or 4 mg once daily) is sufficient to inhibit AAK1, thus it has been suggested to be trialed in an appropriated COVID population [6,292]. On the other hand, therapies targeting JAK complexes may interfere with normal anti-viral response including inhibition of IFN-γ activity and may potentially increase the risk of infection and/or reactivation of several viral infectious diseases [293][294][295], including a dose dependent risk for VZV observed for tofacitinib and baricitinib [296]. Thus, their usage should be carefully evaluated.…”
Section: Janus Kinases Inhibitorsmentioning
confidence: 99%
“…Baricitinib, at therapeutic dosing (either as 2 mg or 4 mg once daily) is sufficient to inhibit AAK1, thus it has been suggested to be trialed in an appropriated COVID population [6,292]. On the other hand, therapies targeting JAK complexes may interfere with normal anti-viral response including inhibition of IFN-γ activity and may potentially increase the risk of infection and/or reactivation of several viral infectious diseases [293][294][295], including a dose dependent risk for VZV observed for tofacitinib and baricitinib [296]. Thus, their usage should be carefully evaluated.…”
Section: Janus Kinases Inhibitorsmentioning
confidence: 99%
“…The current review finally highlights the role of IFN-c in the adverse events seen with JAK inhibition. An increased risk of herpes zoster is most specifically related to the use of JAK inhibitors among patients with RA or other immune-mediated diseases [56,57]. It is also worth noting that the risk of infection with other viruses, such as cytomegalovirus and Epstein-Barr virus, has not been increased with JAK inhibition [58], suggesting a special connection between JAK-STAT pathway and immunity to VZV.…”
Section: Ifn-c In Varicella Zoster Virus (Vzv) Infectionmentioning
confidence: 99%
“…However, we observed that JAK inhibitors enhanced cellular infection of SARS-CoV-2 at higher concentrations, suggesting an effect on interferon signaling, a possible clinical liability that should be closely monitored during trials. Supporting this finding and underlining the importance of identifying diverse options to address cytokine storm, JAK inhibitors are known to increase the prevalence or severity of other viral infections including herpes zoster, JC virus, and hepatitis B [73][74][75] . This study also identified alternative mechanisms of action which have been much less deeply considered in the context of COVID-19, such as certain Syk inhibitors, c-Met inhibitors and PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 81%